Fraccionamiento de metales y materia orgánica en un suelo de la Península de Paraguaná, estado Falcón, Venezuela. - Acosta, Yudith; Paolini, Jorge; Flores, Saúl; El Zauahre, Maziad; Reyes, Nicolás; García, Hendrina (Multiciencias)
Ver resumen pdf.